BARRIERS AND OBSTACLES IN IMPLEMENTING MEMORIZED METHOD FOR LEARNING ENGLISH DURING COVID-19 PANDEMIC - Hani Suryani; Cynantia Rachmijati (IKIP Siliwangi, 2022)
Pandemic covid-19 gave big impact to teaching and learning process, government has stated during pandemic , teaching and learning process conduct with online strategy. All off silabus school adopted new strategy to implemented the goverment stated. This journal, explained about the process of teaching and learning English and learning to memorized which was carried out online during the Covid -19 pandemic. Where the problem is that some students do not understand the material, therefore the researcher tries to find and analyze data about these difficulties. The questions of this research are (1) What are the students' problems in online learning? (2) What are the obstacles and constraints in using memorization techniques?. The aims of this study is to explained barriers and obstacles using memorized method during teaching and learning online process . This study used a qualitative descriptive, data take from other literatur in Madrasah Ibtidaiyah Ummul Qura and own research at SMP Advent Naripan Bandung. From the two questions used, the researcher gets the results that show the difficulty of the students. Forms of barrier and obstacles that are obtained are, (1) students' difficulties in remembering, (2) lack of students concentration, (3) students are lazy to memorize, (4) students lack enthusiasm in memorizing, (5) limited quota, (6) consistency of networking, handphone problem (telecommunication aspect), (7) students late attendance to the online learning process, (8) lack of student focus, (9) dislike of english subject ( Mindset of the Students ). Keywords: Barriers and Obstacle, English Learning, Memorized Technique